Implementasi Bantuan Dana Usaha Kredit Rakyat(KUR) dan Regulasi Perbankkan Terhadap Pendapatan UMKM Pada Nasabah BanK Sulselbar - Hariatih, Hariatih; Payu, Anita Achmad; Lisda, Lisda (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
This research aims to analyze People's Business Credit Fund Assistance (KUR) and banking regulations on Micro, Small and Medium Enterprises (UMKM) Income for PT Customers. Bank Sulselbar Bantaeng Branch The research method used in this research is a qualitative research method, the type of research used is field research, the research approach is a case study approach, this research data was obtained from primary data and secondary data. The data collection techniques used were observation, interviews and documentation. The data analysis technique used is qualitative data analysis. The results of the research show that the implementation of Bank Sulselbar Bantaeng Branch business credit assistance in distributing People's Business Credit (KUR) to Micro, Small and Medium Enterprises (UMKM) has increased very significantly and requires government intervention in banking regulatory policies by making several regulations that will be included in banking law so that micro, small and medium enterprises (UMKM) can more easily develop their businesses with capital assistance in the people's business credit program (KUR) and increase banking interest rates on people's business credit (KUR)